Rapid 3D measurement using digital video cameras - Van der Merwe, Willem Johannes (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2008.